Insight into the uptake and metabolism of a new insecticide cyetpyrafen in plants. (November 2022) - Li, Runan; Wang, Sijia; Chang, Jinhe; Pan, Xinglu; Dong, Fengshou; Li, Zhiyuan; Zheng, Yongquan; Li, Yuanbo
Graphic abstract: Highlights: Uptake and metabolism of a new pesticide cyetpyrafen in crops were firstly explored. Cyetpyrafen was mainly accumulated in roots likely through passive diffusion process. Thirteen new metabolites of cyetpyrafen were firstly identified in plants. Cyetpyrafen mainly underwent hydroxylation, hydrolysis and conjugation in crops. Phase I metabolites were estimated to be harmful/toxic toward nontarget organisms. Abstract: As new agrochemicals are continuously introduced into agricultural systems, it is essential to investigate their uptake and metabolism by plants to better evaluate their fate and accumulation in crops and the subsequent risks to human exposure. In this study, the uptake and elimination kinetics and transformation of a novel insecticide, cyetpyrafen, in two model crops (lettuce and rice) were first evaluated by hydroponic experiments. Cyetpyrafen was rapidly taken up by plant roots and reached a steady state within 24 h, and it was preferentially accumulated in root parts with root concentration factors up to 2670 mL/g. An uptake mechanism study suggested that root uptake of cyetpyrafen was likely to be dominated by passive diffusion and was difficult to transport via xylem and phloem. Ten phase I and three phase II metabolites of cyetpyrafen were tentatively identified in the hydroponic-plant system through a nontarget screening strategy. The structures of two main metabolites (M-309 and M-391) were confirmed by synthesized standards. The metabolic pathways were proposed including hydroxylation, hydrolysis, dehydrogenation, dehydration and conjugation, which were assumed to be regulated by cytochrome P450, carboxylesterase, glycosyltransferase, glutathione S -transferases and peroxidase. Cyetpyrafen and its main metabolites (M-409, M-309 and M-391) were estimated to be harmful/toxic toward nontarget organisms by theoretical calculation. The high bioaccumulation and extensive transformation of cyetpyrafen highlighted the necessity for systematically assessing the crop uptake and metabolism of new agrochemicals.